2020
DOI: 10.1093/jnci/djaa155
|View full text |Cite
|
Sign up to set email alerts
|

“When Offered to Participate”: A Systematic Review and Meta-Analysis of Patient Agreement to Participate in Cancer Clinical Trials

Abstract: Background Patient participation in clinical trials is vital for knowledge advancement and outcomes improvement. Few adult cancer patients participate in trials. Although patient decision-making about trial participation has been frequently examined, the participation rate for patients actually offered a trial is unknown. Methods A systematic review and meta-analysis using 3 major search engines was undertaken. We identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
117
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(127 citation statements)
references
References 75 publications
(46 reference statements)
8
117
2
Order By: Relevance
“…Despite greater odds of reported invitation to clinical trials in this study, non-Hispanic Black respondents had lower odds of reported participation in clinical trials than non-Hispanic White respondents. This contrasts with previous work showing Black and White individuals enroll in clinical trial at similar rates if invited 30,31,38,39. Although our study controlled for comorbidity status, health…”
contrasting
confidence: 90%
“…Despite greater odds of reported invitation to clinical trials in this study, non-Hispanic Black respondents had lower odds of reported participation in clinical trials than non-Hispanic White respondents. This contrasts with previous work showing Black and White individuals enroll in clinical trial at similar rates if invited 30,31,38,39. Although our study controlled for comorbidity status, health…”
contrasting
confidence: 90%
“…Unger et al have recently identified this as a key distinction to acknowledge in determining demographic disparities in trial accrual rates. 33 Although our data showed that almost twice as many women than men reported that they would not necessarily participate in a research study due to COVID-19, this observation had limited statistical power and was not significant.…”
Section: Discussionmentioning
confidence: 59%
“…One key barrier to participation that has been previously identified is travel concerns (16,18). It is of concern that in our COVID-19-specific study, a crucial factor that seemed to be underlying participants' willingness to undertake inperson visits was car ownership, implying that the presence of COVID-19 may compound previously observed logistical issues related to transport.…”
Section: Discussionmentioning
confidence: 81%
“…In Viljoen et al's qualitative review, such factors included: (1) the patient's degree of trust and confidence in their healthcare professionals; (2) the style of communication of information about the trial between physician and patient (which, when suboptimal or rushed, could lead to patients feeling uninformed and alienated); (3) the sense of moral obligation, or altruism, towards society; and (4) the reassurance that they will be adequately cared for during study procedures. Further patient-level factors that may influence risk-to-benefit appraisal in this setting have been recently documented by other investigators, and these include a fear of treatment sideeffects; disliking the idea of being experimented upon; issues or complications arising from travel to the study site; burden of study procedures (including emotional burden); knowledge about the study/intervention; concerns about the physical setting of the study; and physician's attitude towards the study (14,16,18). It is conceivable that patients' considerations related to the COVID-19 pandemic may modify their experience, or appraisal, of several of these identified factors.…”
Section: Introductionmentioning
confidence: 94%